Mitigating Bangladesh's Power Crisis : Possible Response Options - A Briefing Note for the Ministry of Finance - World Bank (Washington, DC, 2012)
Bangladesh today is in the grips of a major power crisis. There are several dimensions to the crisis: operational, financial and relating to power generation. This report includes the following headlines: past responses, what can be done to mitigate the crisis? Recommend short-term priority actions, medium-term policy priorities, and issues requiring attention for the Fourth Development Support Credit Project (DSC 4).